40.0k views
3 votes
10x + 8y = -6
-2x − 8y = -18

User Nard Dog
by
5.0k points

2 Answers

2 votes
Answer is ( -3,3 ) .
User Merovex
by
5.1k points
5 votes

Answer:

(-3,3)

Explanation:

10x + 8y = -6

-2x − 8y = -18

Add these two equations together to eliminate y

10x + 8y = -6

-2x − 8y = -18

------------------------

8x = -24

Divide each side by 8

8x/8 = -24/8

x = -3

Now we need to find y

10x + 8y = -6

Substitute x =-3

10 (-3) + 8y = -6

-30 +8y = -6

Add 30 to each side

-30+30 +8y = -6+30

8y = 24

Divide by 8

8y/8 = 24/8

y =3

(-3,3)

User Rasoul Zabihi
by
5.2k points